The Bureaucratization of Zakāt and the Illusion of Justice: Symbolic Politics in Indonesia - Abd. Karim Amirullah, Malik; Kamaluddin; La Abdul Zayl; Slamet Haryono (Millati: Journal of Islamic Studies and Humanities, 2025)
This article presents a critical interrogation of the transformation of zakāt in Indonesia, examining the shift in its function from a theological ethical imperative to an administrative instrument laden with symbolism. By analyzing the legal framework, public campaigns, BAZNAS reports, and enriched by in-depth interviews, the study reveals that the current practice of zakāt fails to ensure substantive justice. Instead, the process gives rise to a performative narrative that showcases success as a strategy for institutional moral legitimation. Drawing a theoretical lens from Timur Kuran and John Rawls, the research argues that the selection of mustahīk is distorted; recipients are chosen based on their readiness to participate in visual logic, rather than on the depth of their need. Zakāt now operates as a field of representation, determining who is constructed as "empowered" and who is silenced. These findings call for the institutionalization of the ’theology of discomfort’, where performance indicators must prioritize inclusion over spectacle, and zakāt institutions must recognize unquantifiable vulnerabilities (such as trauma and social exclusion). The article concludes with a call for the reclaiming of the radical ethic of zakāt, focusing on the mustahīk who are unheard and unaccounted for in the dominant narrative of success.